More evidence of the linkage between face processing and language processing. - Pascalis, Olivier; Dole, Marjorie; Lœvenbruck, Hélène (British Journal of Psychology, 2017)
This review of the literature on the emergence of language describes two opposing views of phonological development, the sound-based versus the whole-word-based accounts. An integrative model is proposed which claims that learning sublexical speech sounds and producing wordlike vocalizations are in fact parallel processes that feed each other during language development. We argue that this model might find unexpected support from the face processing literature.